PENGARUH PROACTIVE PERSONALITY, KNOWLEDGE SHARING, DAN OPENNESS TERHADAP INNOVATIVE WORK BEHAVIOR PADA KARYAWAN PERUSAHAAN X - Azzahra, Alivia; Amar, Faozan; Zainita, Amilia; Pelita, Pepi Januar (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
The ever-growing era of globalization creates increasingly fierce competition in the world of work. To survive and excel, organizations need to encourage innovation through innovative work behavior. Some of the main factors that can influence this behavior include proactive personality, knowledge sharing, and openness, which contribute greatly to the creation of an innovative and productive work atmosphere. This study aims to analyze the correlation between proactive personality, knowledge sharing, and openness to innovative work behavior. The approach used was quantitative, involving 100 employees as respondents, while data were collected through a questionnaire survey. The results of the analysis show that proactive personality, knowledge sharing, and openness contribute positively and significantly to innovative work behavior, both in partial and simultaneous analysis. The findings confirm the importance of encouraging proactive personality, knowledge sharing, and openness in organizations to enhance employees' innovative capacity.